Une approche psycho-anthropologique des savoirs à l' "école de la vie" chez des adultes peu ou pas scolarisés au Brésil - Laurendon, Candy Estelle Marques (2018)
The principal aim of the thesis is to describe the conditions of acquisition of the knowledge at the “school of life” by Brazilian little or no schooled adults. The expression “school of life” commonly used by Brazilian people of popular social class stresses the importance of daily life for learning as opposed to the School where these people are usually in school failure. By adopting a psycho-anthropological approach (participative observation of daily and professional activities and life narratives), two studies have been conducted focused initially on numeric knowledge. The first study concerns the daily activities of six migrants women from the countryside living in the suburbs of Porto Alegre: budget management and market exchanges. The second study focuses on the trader’s professional practice of fruits and vegetables followed for six months, from the products purchase to the sale at a Recife’s market. The analysis of the interviews data (video recordings transcribed) and the observations recorded in a daily diary are based on the Barbara Rogoff‘s theorical framework (1995) that distinguishes three levels: institutional or community level, inter and intra-personal levels. It appears that participation structures are various: peers’ collaboration, quasi-teaching by the employer, skills transmission to younger generations. The numeric knowledge are embedded into a constellation of knowledge. The subjects create or adapt a variety of instruments for their activities.